A study on factors that influencing brand loyalty toward sportswear product in Johor / Nurul Farhana Hamzari - Hamzari, Nurul Farhana (Faculty of Business and Management, 2016)
The purpose of the study is to determine the relationship between seven independent variables which is brand names, product quality, price, style, promotion, service quality and store environment with the dependent variable is a brand loyalty. The research was carried out by using the 5 point Likert Scale Measurement in gathering the data. Quantitative approach methods were applied in this survey for citizens in Kulai, Johor. Questionnaire were using as a research instruments. 380 of respondents in Kulai, Johor were selected as a sample size for this study in order to answer the distributed questionnaires. SPSS software version 2.0 was used to analyze the data. There are some analysis are included which is Frequency analysis (Demographic Analysis), Reliability Analysis, Descriptive Analysis, Pearson Correlation Analysis and Multiple Regression Analysis. The finding of the study shows that there are strong positive significant relationships of product quality with the brand loyalty on the sportswear product in Johor.